An Experimental Study of OTT–Influencer Effects and Cultural Moderation for Indonesia’s Culinary Nation Branding - Hidayatullah, Muhammad; Awaluddin, Muhammad; Firdaus, Acmad; Suherman, Ansar (Universitas Muhammadiyah Yogyakarta, 2025)
This study compares OTT and influencer advertising across Malaysia and Russia and examines how cultural proximity shapes destination-marketing outcomes. A 2×2 between-subjects experiment (OTT vs. influencer × Malaysia vs. Russia) was conducted with online adult participants. The results show a significant main media effect on visit and purchase intention, as well as a Media × Culture interaction: influencer advertising performs better in Malaysia, whereas OTT performs better in Russia. Cultural proximity is positively associated with ad attitude, intention, and destination brand equity, and it also amplifies media effects. Practically, in markets similar to Malaysia, organizations should prioritize influencer-led strategies featuring culturally resonant creators. In markets similar to Russia, they should anchor reach and frequency through OTT, complemented by curated influencer activations. Overall, the findings clarify an operational bridge between nation-branding objectives, straightforward reach–frequency planning, and cultural proximity.